A Discussion Paper on Indigenous Custom Adoption Part 1: Severed Connections – Historical Overview of Indigenous Adoption in Canada - di Tomasso, Lara; de Finney, Sandrina (First Peoples Child & Family Review, 2015)
This paper forms Part 1 of a two-part discussion paper on Indigenous custom adoption. Zeroing in on the entangled histories of adoption and colonization, it outlines a short history of adoption in Canada, examines the impact of forced, closed, and external adoptions on Indigenous adoptees, and traces the move toward more open statutory adoptions and greater cultural connection and continuity in adoptions. This historical review sets the stage for Part 2 of our discussion paper, “Honouring Our Caretaking Traditions,” where we highlight the connections between customary laws regarding caregiving and the resurgence of Indigenous authority over child welfare within a context of Indigenous self-determination and self-governance.